FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS KARET PERKEBUNAN RAKYAT (Kasus Perkebunan Rakyat di Kecamatan Tulang Bawang Tengah Kabupaten Tulang Bawang, Lampung) - Wiyanto, Wiyanto; Kusnadi, Nunung (Jurnal Agribisnis Indonesia, 2013)
This researchÂ compared rubber quality between smallholder rubber farmers in rubber development program village and non-program village. The objectives of the research were to identify cause of low-quality rubber, identify farmerâs efforts to increase rubber quality, to describe and to test relationship betweenÂ socioeconomic characteristics of the farmers, technical factors, and rubber quality among them, and to analyze farmer benefit after use of rubber quality technology. Data for the research were generated from 64 respondents randomly from three villages. Descriptive statistics, qualitative analysis, binary logistic regression model, and partial budgets analysis were used in analysing the data. The result of analysis showed that farmers in program village produced lower grade rubber (average 6.13) than farmers in non-program village (average 6.98). The identification result suggest that the causes of low-quality rubber were the use of coagulant other than formic acid, use of additive coagulant and existence of contaminants in coagulump. The empirical result revealed that majority of farmers did efforts to increase rubber quality such as cleaning of collecting pans periodic, keeping of coagulump from contaminants, but just minority of farmer used trained tappers, cleaning of collecting cups before tapping, dissociating types of coagulump and there were no farmers using of formic acid as coagulant. The qualitative analysis and binary logistic regression model indicated relationship between education, family size, membership of farmer institution, participation in social activities and rubber quality at 20% probability level. The partial budgets analysis proved that use of formic acid as coagulant was profitable in program village and non-program village.